2021
DOI: 10.1108/cg-05-2021-0201
|View full text |Cite
|
Sign up to set email alerts
|

Social media fostering happiness management: three luxury brands case study on Instagram

Abstract: Purpose This paper aims to increase the understanding of luxury brands’ branded content strategies concerning follower's engagement generated or not by happiness and well-being feelings spread in their branded content. Design/methodology/approach This study sample was composed of three of the most relevant luxury brands nowadays: Manolo Blahnik, Loewe, y Balenciaga. To address this research, an exploratory-correlational quantitative methodology was chosen; hypotheses were contrasted using ANOVA analysis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…Furthermore, given the benefits of social marketing and happiness management for increasing the competitiveness of a firm [57][58][59], customizing promotional content is more effective if it gives consumers feelings like happiness and well-being [60]. In this way, users are more attracted to the ads that make them feel good, making the social media marketing campaign more effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, given the benefits of social marketing and happiness management for increasing the competitiveness of a firm [57][58][59], customizing promotional content is more effective if it gives consumers feelings like happiness and well-being [60]. In this way, users are more attracted to the ads that make them feel good, making the social media marketing campaign more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Social marketing is considered a powerful tool of which the main purpose is to increase 'social good' by changing people's behaviour in order to increase social well-being and happiness [59]. A study showed that followers' engagement increases on social media if the brand content is linked to concepts such as happiness and health and safety [60]. "Social media have been developed rapidly and it is recognized as a key strategic element of organizations competitiveness and survival" [61], and its value is recognized in various fields [62][63][64], being related to happiness and consumption habits [65].…”
Section: Smm and The Personalisation Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportunities provided by social media for companies and brands to communicate with users and potential clients has increased the use of social media and the creation of branded content as an essential tool in the digital communication process, promoting an extensive transformation in the way brand content is created, distributed, and released (Núñez-Barriopedro et al, 2013;Wahid & Gunarto, 2021). Moreover, communication processes have been enhanced by the direct dialogue offered by social media among brands and clients, becoming two-way and real-time interactions favored by the penetration of networks among all the populations that use them intensively, and promoting different experiences such as happiness (Castillo-Abdul, Pérez-Escoda, & Civila, 2021;Cuesta-Valiño et al, 2021), positive feelings (Casaló et al, 2020), or sharing attitudes (Choi & Lee, 2019). In this sense, social media emerges as a more suitable scenario for maintaining continuous and ubiquitous communication, establishing an in-depth relationship with audiences that demand increasing amounts of information from brands (Castillo-Abdul, Bonilla-del-Río, & Núñez-Barriopedro, 2021).…”
Section: Fashion Brands and Social Mediamentioning
confidence: 99%
“…The mediation of the internet has extensively modified relationships between brands and customers. Social networks have transformed consumers' role, emerging like active users where brands interact directly with them (Castillo-Abdul, Pérez-Escoda, & Civila, 2021). Branded content as a network marketing technique is firmly positioning itself in the online environment not only as an effective strategy for the creation of content related to brands (Chen & Shupei, 2019), but also as an effective narrative tool in the fight against the recent phenomenon known as infodemic, which emerged and was fostered during the Covid-19 pandemic situation with fake news (Pérez-Escoda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%